Overseas management in the English East India Company: a study of the Tonkin factory (1672-1697) - Tran, Ngoc Dung; Dinh, Phuong Hoa; Nguyen, Dinh Hoang Uyen; Nguyen, Van Vinh (Journal of management history, 2023)
Purpose This paper aims to investigate “corporate governance” of the English East India Company (EIC) in the late 17th century through a case study of the Tonkin factory (1672–1697). Design/methodology/approach The paper draws upon British primary materials relating to the Tonkin factory to examine and analyze the EIC’s style of management in Tonkin (Vietnam) and Bantam (Java). Qualitative and comparative methods are applied to the analysis of reports, records and letters written by EIC staff. Findings The paper finds that the EIC faced principal-agent problems as it had difficulties administering its distant agents and subsidiaries in the 17th century. London was strategically weakened, both by the limiting power of regional headquarters and by its use of experienced factors. Before 1682, London failed to temper the Bantam Council’s influence, and there were serious internal conflicts and power struggles between English Tonkin employees seeking to improve their positions. After 1686, London successfully forced Madras to adopt a noninterventionist stance in Tonkin’s business, but it faced the problem of “adverse selection.” Originality/value This paper provides evidence from the Tonkin factory (1672–1697) to show the EIC’s governance in the perspective of the agency theory.